Digital literacy of Heart Communication for reducing bullying model - Lestari, Puji; Ediningsih, Sri Isworo; Setyowati, Yuli; Prakanto, Rudy; Suryawijaya, Priyahita Garmadyuti; Ardiyanti, Vanissa Zera (Association for Scientific Computing Electrical and Engineering (ASCEE), 2024)
One of the most worrying forms of juvenile delinquency is bullying. Heart communication integrated with digital literacy is a solution to overcome bullying. This study aims to analyze the effect of heart communication digital literacy on reducing bullying behavior in 30 Senior High Schools and Vocational High Schools (Jogja Smart School) in the Special Region of Yogyakarta and to find a Heart Communication Digital Literacy model to reduce bullying. The theories used are Heart Communication Theory, Digital Literacy Theory, and Cognitive Theory. This study uses mixed methods sequential explanatory, which begins with quantitative methods and then qualitative methods. Quantitative methods with surveys on a sample of 400 students as research subjects. Quantitative data analysis techniques use regression analysis. Qualitative methods include interviews and FGD techniques, and data analysis is done using the Miles and Huberman method. The results of quantitative research show that the heart communication digital literacy variable with the dimensions â€œTahu Komunikasi Hati,â€ â€œTanggap Komunikasi Hati,â€ and â€œTangguh Komunikasi Hatiâ€ has a significant contribution to reducing bullying behavior, with an R Square value of 28%. This study concludes that the Heart Communication Theory has been proven to reduce bullying in Jogja Smart School Senior High School and Vocational High School students in the Special Region of Yogyakarta. The results of qualitative research found a novelty in the form of a digital literacy of heart communication to reduce bullying model.